Application of biotechnology for processing mineral deposits of Tuva - Mongush, Grigory R. (The New Research of Tuva, 2010)
The concept of "biotechnology", its development and transformation among with the possibility of its application in hydrometallurgy is considered in the article. The method of application of bacteria is described at biolixiviation of precious metals. Article offers the technological scheme of processing arsenic waste at the "Tuvacolbalt" industrial complex.